Fenomenologis Keluarga Berencana Di Lingkungan Yayasan Pondok Pesantren Nurud Dholam Dalam Membentuk Keluarga Harmonis (Studi Kasus di Palengaan laok Kabupaten Pamekasan) - Rozi, Fahrur (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2023)
This study discusses Family Planning in the environment of the Nurud Dholam Palengaan Laok Pamekasan Islamic Boarding School Foundation which follows the Family Planning program has reasons to form a Harmonious family. The reasons for the family congregation are based on economic, health and psychological reasons. The reason is because it has a positive impact so that children's education is fulfilled optimally, they love each other, understand each other and all members understand their rights and obligations. Likewise, from the negative impact side, families who implement Family Planning, namely preventing pregnancy, are equally permitted, as long as the method does not harm health. Along with the development and progress achieved and known by mankind. It turns out that many tools, methods and facilities are found that are similar to 'Azl as used by the Jamaah Jamaah in the Nurud Dholam Palengaan Laok Islamic Boarding School Foundation environment to prevent pregnancy. One of the modern methods used by the Jamaah is the Hormonal method (Pills and Injections) which has side effects on the health of KB acceptors, health will be disturbed such as coughing, obesity and others. The goal is to maximize their children's education.